A review on multiple functions of ionic liquid in biodiesel production - Mohamed Sharikh, Atikah; Sulaiman, Sarina; Azmi, Azlin Suhaida (Penerbit Akademia Baru, 2017)
Scarcity of petroleum and constant concern over environmental problems caused by diesel fuels has promoted production of biodiesel from renewable sources. Biodiesel synthesized from transesterification methods in the presence of acid or base catalyst or enzyme requires huge amount of solvent, particularly from alcohol to affirm high production yield. Inevitably, the process results in bulky waste that demands appropriate attention. In attempt to tackle the problem, ionic liquid has been identified to be the most potential substitute for conventional catalyst and solvent required in the biodiesel conversion. Ionic liquid that is widely known as ‘green chemical’ can be synthesized to meet reaction requirement by careful selection of anion and cations, with correct proportion of each to produce desired mixture. This paper reviews recent applications of ionic liquid in biodiesel production as catalyst, solvent and co-solvent. Since there are few ways in which ionic liquid can be categorized, this paper highlights classification of ionic liquids into two major groups; namely acidic and basic ionic liquid. Discussion on these tswo groups covers their dual- functions in biodiesel production which are as solvent or co-solvent and catalyst as well as the limitation of each group in the biodiesel production.